2019
DOI: 10.1177/1559325819876780
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Transcriptome Analysis Reveals Intermittent Fasting-Induced Metabolic Rewiring in the Liver

Abstract: Scope: Intermittent fasting (IF) has been extensively reported to promote improved energy homeostasis and metabolic switching. While IF may be a plausible strategy to ameliorate the epidemiological burden of disease in many societies, our understanding of the underlying molecular mechanisms behind such effects is still lacking. The present study has sought to investigate the relationship between IF and changes in gene expression. We focused on the liver, which is highly sensitive to metabolic changes due to en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 34 publications
2
19
0
Order By: Relevance
“…S2). Among those, we found several GO terms consistent with previous fasting studies, including carboxylic acid biosynthetic process, lipid homeostasis, xenobiotic metabolism, regulation of protein stability, and regulation of protein localization to membrane [13,16,35]. Interestingly, we also identified other novel pathways enriched by STF, such as wound healing, sensory perception of pain and positive regulation of vasculature development, thus highlighting the discovery potential of this approach.…”
Section: Organ-specific Modulations By Stfsupporting
confidence: 85%
See 1 more Smart Citation
“…S2). Among those, we found several GO terms consistent with previous fasting studies, including carboxylic acid biosynthetic process, lipid homeostasis, xenobiotic metabolism, regulation of protein stability, and regulation of protein localization to membrane [13,16,35]. Interestingly, we also identified other novel pathways enriched by STF, such as wound healing, sensory perception of pain and positive regulation of vasculature development, thus highlighting the discovery potential of this approach.…”
Section: Organ-specific Modulations By Stfsupporting
confidence: 85%
“…The advent of high-throughput omics facilitated the elucidation of some of the cellular and molecular mechanisms underlying the beneficial effects of fasting. Nonetheless, the majority of these studies focused on single organ response (i.e., the liver) and, less often, involved two or three organs [10][11][12][13][14][15][16]. The adaptation to energy deprivation, however, requires a multi-organ integration of metabolic modulations to protect the organism from an irreversible loss of resources [17].…”
Section: Introductionmentioning
confidence: 99%
“…Activated AMPK induces a series of events resulting in reduced fatty acid synthesis, oxidation, and cholesterol synthesis, but active SIRT1 may increase ketogenesis and lipolysis, and decrease glycolysis. Other proteins can be involved in these processes [95].…”
Section: Epigenetic Link Between Nutrition Aging and Cancermentioning
confidence: 99%
“…Recently, Hernando-Herraez showed that mouse stem cells acquire epigenetic drift by the accumulation of stochastic changes of DNA methylation in the promoters of many genes, which leads to altered transcriptional control and the aging of stem cells [97]. Epigenetic mechanisms of anti-aging effects resulting from CR were then postulated and shown in several works [5,91,94,95,[98][99][100].…”
Section: Epigenetic Link Between Nutrition Aging and Cancermentioning
confidence: 99%
“…Thus, it may counteract both ROS generation and effects [217,218]. Of note, it has been widely demonstrated that the beneficial effects of caloric restriction are also mediated by epigenetic mechanisms [219,220], that, as previously described, are tightly linked with the oxidative status of the cell.…”
Section: Antioxidants and Mitochondria: From The General Function To mentioning
confidence: 94%